The Response of MENA Country Stock Markets to the Conflict in the Red Sea: Evidence from an Event Study Approach - altemur, necati; doğan başar, berna; ekşi, ibrahim halil (The Indonesian Capital Market Review, 2024)
The impact of Houthi attacks on commercial vessels in the southern Red Sea and the Gulf of Aden on the stock markets of 10 MENA countries is analyzed using an event study. The event day is 10.01.2024, when the Houthis announced targeting the US navy. Significant results are found regarding stock market efficiency and portfolio investors. The t-test shows that CAR (Cumulative Abnormal Return) values are statistically significant for some MENA countries. Positive abnormal returns are found in Morocco, Bahrain, and Egypt, while negative abnormal returns are found in Lebanon and Tunisia within the event window. In other countries analyzed, no significant effect of the event on stock returns is observed.